The Assessing Cimenyan Village's IT Readiness for Digital Transformation in West Java - Majapahit, Sali Alas (Universitas Bina Darma, 2023)
Digital Village Development has become an important agenda in efforts to modernize and improve the quality of life in rural areas. This transformation relies on the use of information and communication technology (ICT) to increase convenience and efficiency in various fields. The success of developing a Digital Village depends on the readiness of ICT infrastructure. The village office, which is the center for administration and services to the community, must have adequate ICT infrastructure as the main requirement for activating various digital initiatives. The research was conducted to determine the current state of readiness of Cimenyan village, Bandung Regency in implementing ICT in village government offices. The readiness level analysis is prepared based on the COBIT framework in 3 domains, namely: IT process domain PO1 (defining IT strategic plans), PO2 (determining information architecture), and PO4 (defining IT processes, IT organization, and their relationships) The results of the analysis will be mapped based on the maturity level of each domain in COBIT. The level of maturity obtained will help the Cimenyan Village government to make appropriate preparations for implementing ICT so that the goal of Cimenyan Village becoming a digital village in West Java can be achieved.